Effect of ATH filler on the electrical tracking and erosion properties of natural rubber-LLDPE blends under wet contaminated conditions - Md Piah, Md Afendi; Darus, Ahmad; Hassan, Azman (Fakulty Electrical Engineering, Universiti Teknologi Malaysia, 2004)
Polymeric insulators are increasingly being accepted by electric utilities worldwide. The tremendous growth in the application of polymeric insulators is due to their substantial advantages compared to porcelain and glass insulators. This paper describes the electrical surface tracking and erosion behaviour of newly formulated thermoplastic elastomer (TPE) materials with different levels of alumina trihydrate (ATH) content. Natural rubbers blended with linear low-density polyethylene (LLDPE) at different weight ratios were used as base polymer of the TPE materials. An electrical tracking and erosion test according to IEC 587 or ASTM D2303 was conducted to study the characteristics of leakage current on the material surface under wet-contaminated and electrical stress conditions. Morphological analysis was carried out to relate the surface tracking properties with the surface morphology before and after-the tracking test. Certain characteristics of the electrical discharge contributed to the tracking phenomenon. Experimental results showed the blends filled with different levels of ATH significantly influenced the surface tracking and erosion properties. ATH content of 50 pph was found to improve the surface tracking and erosion resistance of the compounds.